2007
DOI: 10.1080/10976640600843330
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Reliability of Atherosclerotic Plaque Volume Measurements in Peripheral Arterial Disease with Cardiovascular Magnetic Resonance

Abstract: A high resolution, noninvasive approach to quantify atherosclerotic plaque in the peripheral vasculature could have significant clinical and research utility. Seventeen patients with peripheral arterial disease (PAD) were studied in a 1.5T CMR scanner. Atherosclerotic plaque volume in the superficial femoral artery was measured and interobserver, intraobserver, and test-retest variability determined. Nineteen vessels were studied with mean acquisition time of 13.1 minutes per vessel. Mean plaque volume was 7.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 43 publications
1
65
0
Order By: Relevance
“…Furthermore, because plaque volume measured by MRI is highly reproducible, the sample sizes needed to adequately power clinical studies could be dramatically reduced [37]. Excitement over using MRI for this purpose has already spawned several small clinical studies in which MRI has demonstrated significant carotid and aortic plaque regression after treatment with lipid lowering therapy.…”
Section: Mri and Monitoring Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, because plaque volume measured by MRI is highly reproducible, the sample sizes needed to adequately power clinical studies could be dramatically reduced [37]. Excitement over using MRI for this purpose has already spawned several small clinical studies in which MRI has demonstrated significant carotid and aortic plaque regression after treatment with lipid lowering therapy.…”
Section: Mri and Monitoring Therapymentioning
confidence: 99%
“…Choulden et al [49]successfully used high resolution MRI to define the extent of atherosclerotic plaque and characterize the changes that occur with remodeling and restenosis following angioplasty of the popliteal artery. Our group has demonstrated the feasibility and reproducibility of MRI to assess plaque volume in the superficial femoral artery [37] (figure 4). Based on the reliability of the techniques used, sample sizes for clinical trials of atherosclerosis regression could be reduced using this approach [37].…”
Section: Peripheral Artery Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…5,7,[11][12][13] While plaque volume has been reported as an important tool for patient management and for evaluating new therapies, [14][15][16] methods to evaluate this index are limited. 14,15,17,18 Because conventional angiography remains the criterion standard for the diagnosis of vascular diseases, 19,20 techniques that can quantify plaque by using conventional angiography data can be useful.…”
mentioning
confidence: 99%